Assessment of commercial prospectivity of innovative projects - Schwodiauer, Gerhard; Pererva, P. G.; Kosenko, Oleksandra (My University, 2021)
It has been proved that, in the modern sense, the expertise of technology commercialization projects is carried out in the form of a meaningful, qualitative or quantitative assessment of an object intended for use in making managerial decisions. The variety of applications makes the tools used in practice quite flexible. In practice, problems arise (for example, the problem of efficient technology transfer), which are often more complex than those that are solved using traditional approaches.
Оценка коммерческой перспективности инновационных проектов
Keywords: innovative technologies; commercialization; expert assessment; management solutions